2019
DOI: 10.9734/ajrb/2018/v3i329829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methanolic Root Extract of Holarrhena floribunda on the Lipid Profile and Sex Hormones in Wistar Rats

Abstract: Aim: This study aims to determine the effects of methanolic root extract of Holarrehna floribunda on the level of some serum sex hormones, follicle stimulating hormone (FSH), luteinizing hormone (LH), testosterone, estradiol, progesterone and lipid profile in Wistar rats.   Materials and Methods: Twenty- four male and female Wistar rats (150-250 g body weight) were randomly assigned into 4 groups of 6 rats each. Group 1 (control male) took normal rat chow and drinking water. Group 2 (control female) took… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Higher levels of serum lipid may be a result of the disturbance in the regulation of the activity of the hormone-sensitive enzyme, lipase, by insulin due to its deficiency or resistance caused by streptozotocin destruction of beta islet cells 10 . Lipase is inhibited by insulin in the adipose tissues and in the absence of insulin, the plasma level of free fatty acids increases 11 .…”
Section: Results and Discussion Results And Interpretation Of Resultsmentioning
confidence: 99%
“…Higher levels of serum lipid may be a result of the disturbance in the regulation of the activity of the hormone-sensitive enzyme, lipase, by insulin due to its deficiency or resistance caused by streptozotocin destruction of beta islet cells 10 . Lipase is inhibited by insulin in the adipose tissues and in the absence of insulin, the plasma level of free fatty acids increases 11 .…”
Section: Results and Discussion Results And Interpretation Of Resultsmentioning
confidence: 99%
“…Lipid profile testing is carried out [4] to make sure that the body's lipid concentration is normal. Numerous studies on both men and women have found that high density lipoprotein levels in the blood are inversely related to the risk of atherosclerosis [5].…”
Section: Discussionmentioning
confidence: 99%